Pasillos sin luz: Reading the Asylum in Nadie Me Verá Llorar by Cristina Rivera Garza - Kanost, Laura (My University, 2017)
Mexican historian and literary writer Cristina Rivera Garza approaches the space of the asylum not as a monolithic mechanism of rigid control and silence, but as a continual negotiation of bodies and words. The characters in her 1999 novel Nadie me verá llorar improvise their own unique paths through the physical structure of La Castañeda asylum and the sociocultural space of mental illness. Through its narrative techniques, the novel positions its readers, too, in an indeterminate interpretive space. Readers’ paths through the fixed structure of the novel are as idiosyncratic as the characters’ trajectories through La Castañeda and Porfirian society. By representing and fostering such maneuvers—which Michel de Certeau has termed “tactics”—Nadie me verá llorar challenges the subject/object dynamic inherent in conventional concepts of madness. Rivera Garza’s novel manifests a relationship not of reading and writing subjects and voiceless objects, but of interdependent, mutable subjects. Viewed in the context of 1990s mental health care reform initiatives throughout Latin America, the “tactics” at work in Nadie me verá llorar reflect the reality of individuals currently living in psychiatric hospitals, as well as the potential for reform movements to resituate both concepts of mental illness and individuals who are identified as mentally ill.
Citation: “Pasillos sin luz: Reading the Asylum in Nadie me verá llorar by Cristina Rivera Garza.” Hispanic Review 76.3 (2008): 299-316. http://muse.jhu.edu/journals/hispanic_review/summary/v076/76.3.kanost.html
Keywords: Mexican history; Mexico; Cristina Rivera Garza; Asylum; Mental Illness; Nadie Me Verá